2015
DOI: 10.1038/srep13631
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Characteristics of Amyloidogenic Intermediates of β-2-Microglobulin

Abstract: β-2-microglobulin (β2m) self-aggregates to form amyloid fibril in renal patients taking long-term dialysis treatment. Despite the extensive structural and mutation studies carried out so far, the molecular details on the factors that dictate amyloidogenic potential of β2m remain elusive. Here we report molecular dynamics simulations followed by the solvation thermodynamic analyses on the wild-type β2m and D76N, D59P, and W60C mutants at the native (N) and so-called aggregation-prone intermediate (IT) states, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Furthermore, since the number of replicas increases markedly with system’s size, the use of RE-MD is limited to the study of oligomerization of small peptide fragments ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2007 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ). In the case of β2m, MD simulations have been used to study the dynamics of the native monomer ( Ma and Nussinov, 2003 ; Deng et al, 2006 ; Fogolari et al, 2011 ; Chandrasekaran and Rajasekaran, 2016 ), the oligomerization process of selected amyloidogenic β2m peptide sequences ( Liang et al, 2007 ; Zheng et al, 2008 ; Fang et al, 2009a ), and provide complementary information to that obtained through in vitro experiments ( Gumral et al, 2013 ; Chong et al, 2015 ; Torbeev et al, 2015 ; Camilloni et al, 2016 ; Hall et al, 2016 ; Brancolini et al, 2018 ). Another enhanced sampling scheme is the so-called metadynamics ( Laio and Parrinello, 2002 ).…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, since the number of replicas increases markedly with system’s size, the use of RE-MD is limited to the study of oligomerization of small peptide fragments ( Nishino et al, 2005 ; Liang et al, 2007 , 2008 ; Wei et al, 2007 ; De Simone and Derreumaux, 2010 ; Nishikawa et al, 2019 ). In the case of β2m, MD simulations have been used to study the dynamics of the native monomer ( Ma and Nussinov, 2003 ; Deng et al, 2006 ; Fogolari et al, 2011 ; Chandrasekaran and Rajasekaran, 2016 ), the oligomerization process of selected amyloidogenic β2m peptide sequences ( Liang et al, 2007 ; Zheng et al, 2008 ; Fang et al, 2009a ), and provide complementary information to that obtained through in vitro experiments ( Gumral et al, 2013 ; Chong et al, 2015 ; Torbeev et al, 2015 ; Camilloni et al, 2016 ; Hall et al, 2016 ; Brancolini et al, 2018 ). Another enhanced sampling scheme is the so-called metadynamics ( Laio and Parrinello, 2002 ).…”
Section: Computational Models and Techniques Used To Study β2m Aggregmentioning
confidence: 99%
“…In recent years, the Asp76Asn mutant became a valuable model system to study β2m aggregation ( Valleix et al, 2012 ; Chong et al, 2015 ; de Rosa et al, 2015 ; Chandrasekaran and Rajasekaran, 2016 ; Leri et al, 2016 ; Loureiro et al, 2017 ; Le Marchand et al, 2018 ). The reason is twofold.…”
Section: Model Systems To Study β2m Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ham group applied the AD method to their studies about the amyloid-beta protein: hydrohobicity [149], dimerization [150], aggregation [151][152][153], and self-assembly [154]. They also studied about the amyloidogenic potential of β-2-Microglobulin mutant [155], and protein-ligand binding thermodynamics [156].…”
Section: Results Of Rmamentioning
confidence: 99%
“…The strand D has been reported to play a key role in the edgeedge strand association and fibril assembly. 18 Chong et al 19 hydrophobic core residues to solvent in the folded I T -state was reported. 12 The above-mentioned studies emphasized the importance of I T -state for wt β2m and D59P.…”
Section: Introductionmentioning
confidence: 99%